Initiation and intensification of insulin therapy in patients with type 2 diabetes mellitus: a budget impact analysis - E. V. Biryukova; V. I. Ignat'eva (IRBIS LLC, 2017)
To date, several options for starting and intensifying insulin therapy in patients with type 2 diabetes mellitus (T2DM) have been proposed. Meta-analyzes of the recent results shows that, with adequate use, all these regimens have the similar efficacy and safety; therefore, when choosing a therapeutic approach, the patient's requirements and preferences become highly significant. The aim of this study was to assess how changes in the current practice of insulin therapy in patients with T2DM can impact the federal healthcare budget. Materials and Methods. Based on the results of the DURABLE clinical trial, we created a "decision tree" model that allowed us to calculate the costs of 48-week insulin therapy in 1000 T2DM patients who had never received insulin before that trial. The cases selected for modeling included patients on one of two starting regimens - basal insulin (glargine) or a ready-made mixture (biphasic lispro 25). After 24 weeks, upon achieving or not achieving the target HbA1c values, a decision was made whether to intensify the therapy by using the basal bolus therapy (glargine and lispro) or the ready-made mixtures (biphasic 25 or 50 lispro). The weighted average price of 1 IU insulin (according to public procurement data) was used for calculations. Results. Within the current practice of prescribing ready-made mixtures at the start and the intensification rate of 20%, the annual cost of purchasing insulin for the model population of 1,000 patients was 22.5 million rubles. If the use of ready-made mixtures increased to 35% at initiation and to 50% with intensification, the costs would be reduced by by 1.9 million rubles. In the cases when only basal insulin was prescribed for the start, the annual costs amounted to 23.8 million rubles (if only 20% of patients received a ready-made mixture with intensification) and to 22.8 million (if 50% of patients received a ready-made mixture with intensification). Conclusion. As a result of this analysis, an increase in the number of patients who use a ready-made mixture for the initiation or intensification of insulin therapy can lead to reducing the budget costs for purchasing insulin analogues for patients with type 2 diabetes mellitus.